Aplikasi E-Commerce Sebagai Jembatan Perancang dan Konsumen Pada T-Shirt Design - Hendry Hendry; Teddy Marcus Zakaria (Maranatha University Press, 2017)
Abstract — In Indonesia, there is still not a special website that accommodates designers to design, to sell t-shirts with their own design, most websites only sell t-shirts. Abroad, some websites have been selling design t-shirts such as Teespring. Teespring makes it easy to create, sell, and order custom t-shirts, but has the disadvantage that the price is less affordable for the people of Indonesia. T-Shirt Design is an e-commerce website that makes it easy to create, sell and order custom t-shirts with affordable prices. T-Shirt Design embraces designers as sellers with their own design products and accomodate selling their custom t-shirts. T-Shirt Design will process orders from designer/seller and display t-shirt products that have ready to sell to consumer. Consumer can order, buy t-shirt product, and pay it. After receiving the product, consumer will give the feedback that use to improve serving, accuration, expedition. Designer/Seller get selling report, inventory report and list of consumer for each shop. Keywords—Custom T-Shirt, E-commerce, T-Shirt Design